THE EFFECT OF CLOVE STEM OIL (Oleum caryophylli) ON THE GROWTH OF ESCHERICHIA COLI ISOLATED FROM NATIVE CHICKEN, CATTLE AND PIG - Poeloengan, M.; Noor, S.M. (Diponegoro University, 2009)
The objective of this study was to examine the effects of Clove Stem Oil (Oleum caryophylli) orCSO extracts on the growth of Escherichia coli. A 4 x 3 Factorial Design was applied in this study. Thefirst factor was 4 types of E. coli isolates that collected from native chicken (C), young cattle (A), piglet(B1) and pig (B2), while the second factor was 3 concentrations of CSO extract, that was 50.00, 25.00and 12.50 percents. Fifteen micro liters of CSO extract was dropped in sterile paper disks. These diskwere laid on the MEU agar media previously inoculated with each of the four isolates and wereincubated overnight at 370C. The bacterial growth inhibition zones were observed and measured. Theresults demonstrated that the higher concentration of the CSO extracts, the higher bacterial growthinhibition effects obtained. Fhe growth inhibition effects of the CSO extracts on E. coli isolates C, A, B1and B2 were significantly different at P<0.05. It could be concluded that the CSO extracts were effectiveto control the E. coli growth.